Production of bulk NV centre arrays by shallow implantation and diamond CVD overgrowth. Issue 10 (28th July 2016) - Lesik, Margarita; Raatz, Nicole; Tallaire, Alexandre; Spinicelli, Piernicola; John, Roger; Achard, Jocelyn; Gicquel, Alix; Jacques, Vincent; Roch, Jean‐François; Meijer, Jan; Pezzagna, Sébastien
Abstract : The nanometer‐scale engineering of single nitrogen‐vacancy (NV) centres in diamond can be obtained by low‐energy (keV) nitrogen implantation with limited straggling. However, shallow NV centres (a few nanometres deep) generally have inferior overall properties than deeply implanted or deep native NV centres, due to the surface proximity. It has already been shown that the spin coherence time of shallow NVs is improved by overgrowth of a thin diamond layer. However the influence of the overgrowth on the survival, the optical properties and the charge state of the centres has not been studied in detail. In this article, we have overgrown three diamond samples (containing NV centres implanted at different depths) using different procedures. We show the successful overgrowth of a pattern of very shallow (2 nm) implanted NV centres using an optimised overgrowth process. Furthermore, the charge state of ensembles and single NV centres was found to be shifted from NV 0 to NV − and stabilised in the negative charge state after overgrowth. The combination of low‐energy high‐resolution ion implantation and high‐purity chemical vapour deposition (CVD) overgrowth procedures opens the way towards the fabrication of scalable and efficient quantum devices based on single defects in diamond. Left: implanted pattern of very shallow NV centres (depth ∼2 nm) using a pierced AFM tip. Right: same pattern after CVD overgrowth of a 4 μm‐thick diamond layer.